Radio-induced breast angiosarcoma: features of diagnostics and treatment (a clinical case and literature review) - I. V. Kolyadina; V. V. Kometova; Yu. V. Bikeev; S. V. Khokhlova; V. V. Rodionov (Опухоли женской репродуктивной системы, 2020)
Breast angiosarcoma (BAS) is an extremely rare and poorly studied neoplasm, the etiology of primary BAS remains controversial, and secondary BAS is most often radio-induced. Radio-induced breast tumors usually appear 10–20 years after the initial treatment; however, for BAS this period is much shorter and is about 4–7 years. This review presents literature data on the features of the clinic, diagnosis and treatment of BAS, as well as own clinical case observation of radio-induced sarcoma of the left breast, that developed 4 years after the primary breast cancer treatment.